Does literacy status of mother influence breast feeding practices: experience from a semi urban location in Tamil Nadu, India - Mohan, Yogesh; Jain, Timsi; Dutta, Ruma; Parasuraman, Gomathy (International Journal Of Community Medicine And Public Health, 2017)
Background: In spite of regular promotion of breast feeding practices at both National and International level, the proportion of children who are exclusively breast fed during the first 6 months of life is very less. The present study was planned to find out the prevalence of correct breast feeding practices among mothers of 12-23 old children enrolled in Integrated Child Development Scheme (ICDS) centers and to find out its relationship with mother’s literacy status in a semi urban location of Tamil Nadu. Methods: A cross sectional study was done in the ICDS centers. Participants: 127 mothers of 12-23 month old children enrolled in various ICDS centers in the field practice area of Saveetha Medical College. Methodology: Semi structured interviews. Proportion and chi-square were used for analysis. Results: Overall, 19%of the mothers gave pre-lacteal feeds to their babies, 6% of mothers denied colostrums, 12% started complementary feeding before 6 months. Overall literacy status of the mother was associated with better breast feeding practices; however literacy had a complex relation with different aspects of breast feeding. Conclusions: The breast feeding practices were relatively better than reported by other studies in the country. However, still there was a significant gap in correct practices of breast feeding.